Underreported earnings and age-specific income redistribution in post-socialist economies - András Simonovits (Hungarian Academy of Sciences, Institute of Economics, 2009)
We analyze underreported earnings and age-specific income redistribution in postsocialist economies. Pensions, other transfers and public expenditures are financed from contributions and wage taxes, respectively. We derive the reported earnings and savings from individual utility maximization, when workers overly discount the future, obtain partial satisfaction from reporting earnings, cannot be excluded from the use of public services. The government maximizes a utilitarian social welfare function, corrected for discounting and taking into account the utility of public services. An optimal proportional pension system - complemented by appropriate means-testing - provides higher welfare than any system containing a significant flat component.
Keywords: H55; D91; 330; reporting earnings; proportional (contributional) pension; flat pension; progressive wage tax; redistribution; Steuervermeidung; Sozialversicherungsbeitrag; Zahlungsverhalten; Altersvorsorge; Umverteilung; Transformationsstaaten